2017
DOI: 10.1017/cem.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely Canada®: Five tests, procedures and treatments to question in Emergency Medicine

Abstract: The CWC recommendations for emergency medicine were selected using a mixed methods approach. This top 5 list was released at the CAEP Conference in June 2015 and should form the basis for future implementation efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Choosing Wisely Canada (CWC) is a campaign to help patients and healthcare professionals engage in conversations about unnecessary tests and treatments [ 1 ]. On June 2, 2015, the Canadian Association of Emergency Physicians (CAEP) established a list of five CWC recommendations that included the following recommendation: “Don’t order lumbosacral (low back) spinal imaging in patients with non-traumatic low back pain (LBP) who have no red flags/pathologic indicators.” Since then, the CAEP has updated the list to include five more CWC recommendations for emergency department (ED) physicians [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Choosing Wisely Canada (CWC) is a campaign to help patients and healthcare professionals engage in conversations about unnecessary tests and treatments [ 1 ]. On June 2, 2015, the Canadian Association of Emergency Physicians (CAEP) established a list of five CWC recommendations that included the following recommendation: “Don’t order lumbosacral (low back) spinal imaging in patients with non-traumatic low back pain (LBP) who have no red flags/pathologic indicators.” Since then, the CAEP has updated the list to include five more CWC recommendations for emergency department (ED) physicians [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is in agreement with the results of Tama et al (23) which showed that university hospitals had better adherence to the PECARN rule than nonuniversity ones. Another hypothesis could be the successful quality improvement campaigns led independently by the Institut National d'Excellence en Santé et en Service Sociaux (INESSS) since December 2011 (24) and Choosing Wisely Canada (25) since June 2015. These two organizations worked to raise awareness among physicians about the overuse of diagnostic tools and the dangers inherent to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…These two organizations worked to raise awareness among physicians about the overuse of diagnostic tools and the dangers inherent to radiation. As an example, among many published recommendations in June 2015, the first one for Canadian emergency physicians is: "do not order a head CT in children with mTBI unless positively validated with a clinical decision rule (25)".…”
Section: Discussionmentioning
confidence: 99%
“…Of these, approximately 2000 visits are for head injuries. Several national and international organisations have recently highlighted the issue of unnecessary utilisation of diagnostic imaging for patients with minor head injuries, including the Choosing Wisely Canada (CWC) Campaign, the Canadian Association of Emergency Physicians and the American College of Emergency Physicians 1–3. They also recommend the use of validated clinical decision rules to determine when CT scan imaging is necessary 1 2.…”
Section: Problemmentioning
confidence: 99%